NU Online SuperApp and Strengthening Religious Moderation of Nahdlatul Ulama Based on Literacy in the New Media Era 4.0 - M. Khamim (Lakpesdam PCNU Kota Salatiga, 2022)
One of the points of strengthening religious moderation is media literacy. In the era of disruption, the development of religious literacy that contains moderate teachings is urgently needed to balance social media-based conservatism. The need for moderate religious narratives is not only a personal or institutional need, but in general for citizens of the world, especially in the midst of the development of information technology in the face of global capitalism and accelerated politics called the digital era. Currently in Indonesia, there are many online media application features that are aggressively campaigning for the idea of religious moderation, one of which is the NU Online Super App. This article discusses how the transformation and transmission of religious moderation is channeled in the digital realm as a contestation space to seize moderate and tolerant religious narratives through the features of the NU Online Super App. The data collection method used is library research with note taking techniques. The technical analysis of the data used is descriptive analytic. This article aims to examine the role of the NU Online Super App in efforts to strengthen literacy-based Nahdlatul Ulama religious moderation in the new media era 4.0. The results of the study concluded that the NU Online Super App, which is the development of the mobile version of NU Online, is one of the online media that is committed to presenting moderate content and narratives that emphasize the importance of ummah integration, soothing messages, and bringing the message of Islam rahmatan lil 'alamin through the khutbah feature, article feature and more.